DAMPAK ERUPSI TERHADAP INDUSTRI PARIWISATA DI KAWASAN WISATA GUNUNG KELUD KABUPATEN KEDIRI - , SULIS RAHMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mount Kelud is one of the leading tourist attractions in Kediri Regency. The eruption which occurred on 13 February 2014 a few time ago makes Mount Kelud come with a far more different new look than the previous one. In addition, many of the facilities and the tourist attractions suffered damages, even some were lost and buried under the volcanic materials. Since the eruption, the surrounding community who worked in the tourism sector inevitably experienced changes in their income and livelihood patterns. The effects of the eruption on Mount Kelud tourist attraction among others are changing conditions of the tourist attraction, the changing number of visits and economy of the local residents that work in the tourism sector. This study aims to determine the conditions of Mount Kelud tourist attraction after the eruption, the effects of the eruption on the number of tourist visits and the economy of the local residents that work in the tourism sector. This study employed a method of guided interviews with sellers, motorcycle taxiservice providers, lodging owners, managers of Mount Kelud tourist attraction, staffs at the Regional Office of Culture and Tourism of Kediri Regency as well as tourists who visit Mount Kelud tourist attraction. The primary data are the main data for this research. The data analysis was performed using descriptive analysis coupled with tables and figures. Based on the research conducted by the author, it is revealed that there are several effects resulting from the eruption of Mount Kelud which occurred on 13 February 2014, i.e. some facilities, accessibility and attractiveness of Mount Kelud tourist attraction suffered damages, even some of them has been reported missing. Although Mount Kelud has erupted and resulted in many facilities missing, this does not make Mount Kelud tourist attraction lose its attractiveness. Now, Mount Kelud has a new attraction that can bring tourists from various cities, as well as the participation of the local residents to clear the road from the volcanic materials to make access remain reliable and the local residents who depend their life on this tourist attraction are still able to earn a living. In so doing, it can be concluded that Mount Kelud tourist attraction is still worth maintaining, even developing into an interesting tourist attraction in accordance with current conditions.